A Prospective Study to Evaluate the Effectiveness of Prolene Mesh Repair in Incisional Hernia: A Hospital Based Study - Vinod Kumar Jeengar; Rita Verma (Asian Journal of Medical Research, 2020)
Background: Inguinal hernia is the most common diversity accounting for roughly 75% of all hernia. The etiology of an inguinal hernia is clearly not understood. The technique of hernia repair is usually based on custom rather than evidence.4 According to data there is a good observation that open mesh repair is better than suture repair in terms of recurrences. The aim of this study to evaluated the effectiveness of prolene mesh rapair in incisional hernia.Subjects and Methods:A prospective hospital based study done on 30 cases in department of general surgery at RVRS medical college & associated group of hospitals, Bhilwara, Rajasthan. We randomly assigned 30 patients to suture repair or mesh repair of an incisional hernia. The patients were followed up by local physical examination at 1 month & 3 months were done as per standard protocol. Factors related to the operation including the surgical technique, presence or absence of seroma, hematoma, infection, dehiscence were recorded. Follow-up of cases was done at 1 month & 3 months after surgery on an outpatient basis for recurrence of hernia.Results:Our study showed that the majority of cases (43.33%) were seen in 40-49 years of age group. Small (0-5cm) gap size 90% cases and 10% cases have medium gap size in our study. Pain present in 26.66% patients in group A and 20% in group B at 1 month. The recurrence of hernia was present in 28% cases in group A and 4% in group B. It was statistically significant (P=0.0488*) at 3 months and the mostly were well built and have 27.27% wound infection present in these type of patients. Mostly infection occurred in obese patients (40%).Conclusion: We concluded that restoration with polypropylene mesh is superior to suture repair group with concern to the recurrence of hernia.